TBLT's Impact on Primary Learners’ Motivation and Speaking Fluency - Kabita, Most. Nusrat Jahan (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigates the effects of Task-Based Language Teaching (TBLT) on primary English-medium students in Dhaka, focusing on how TBLT helps learners to improve their speaking fluency and learner motivation. The goal of this study was to look into how TBLT affects learners’ motivation and speaking fluency at the primary level. For an in-depth understanding of this matter, a qualitative method was adopted, involving five class observations and interviews with five English teachers. The instruments were validated and pilot tested for consistency. After observing the classes and interviewing the teachers, it is apparent that students become extremely motivated and excited during activity-based classes. Students seemed to enjoy the sessions, and they were cooperating and communicating with the teacher and their peers a lot more than in any regular or traditional classes. After the class observation, the researcher found that students were happy and hopeful to participate in the task, and they were asking for teachers' help to ensure the accuracy of their understanding and performance. Teachers also noticed that, with continuous practice, students were actually improving; they were using longer and more complex sentences with fewer pauses. Overall, TBLT promotes the curiosity of the learners, makes them more interested in learning, and motivates them to communicate more; as a result, their speaking fluency improves naturally. The findings can be helpful if task-based activities are implemented in primary English classes, also in training teachers for designing materials, props to conduct an engaging class, and make sure tasks are culturally relevant and promote collaborative learning, giving constructive feedback and using performance-based assessments to build up students’ motivation level, percentage of participation, and speaking fluency in real-life situations.